RETHINKING THE PAST COMMUNITY DEVELOPMENT OF INDONESIA: HIV TRANSMISSION RISK IMPLICATIONS OF ESTIMATES OF PREMARITAL CONCEPTION - Rahman, Abdul (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2000)
As the countries of Asia and the Pacific come to realize that they will need to confront the AIDS epidemic most are lacking information to help identify populations at risk, and most have no data with which to gauge levels of risk behavior in key segment of the general population. Using data from the 1987 Indonesian Contraceptive Prevalence Survey (The Demographic and Health Survey), we use marital month of first birth to derive estimates of premarital conceptions for marriage cohorts. The estimates produced suggest that the level of premarital sexual intercourse has been rising steadily since the late 1950s, but particularly fast since the mid to late 1970s. Rates specific for age at first marriage and the type of place where a women grew-up, as well as for education suggest that premarital intercourse is now prevalent and increasing rapidly in many segments of the country. The implications of these observations for the development and targeting intervention programs are discussed.